Digital Gambling Marketing and Consumer Behaviour in South Africa: Insights from the Digital Gambling Influence Framework - Michael Mncedisi Willie (University of Science and Computer Technology, 2026)
This study investigates the impact of digital gambling marketing on consumer behaviour, emphasising the interplay among AI-driven personalisation, social media influence, cognitive biases, ethical considerations, and regulatory governance. A narrative literature review was conducted to synthesise evidence on how digital marketing strategies shape consumer engagement, normalise gambling behaviours, and amplify risks among vulnerable populations. Complementing this, a case study of South Africa analysed recent shifts in gambling trends and the sector’s evolving dynamics. Findings reveal that the South African gambling industry has transitioned from traditional casino-based revenue to predominantly digital and mobile betting, illustrating how technological transformation drives consumer behaviour and industry growth. The literature indicates that algorithmic targeting and influencer-led promotions intensify exposure by exploiting cognitive biases, such as the illusion of control and reward anticipation. At the same time, gaps in regulatory oversight and inconsistent enforcement exacerbate potential harm. The study introduces the Digital Gambling Influence Framework (DGIF), a novel conceptual model that integrates marketing stimuli, user vulnerability, ethical boundaries, and governance as interdependent factors shaping individual and societal outcomes. The DGIF offers a theoretical contribution by bridging consumer behaviour, digital ethics, and regulatory governance, providing a structured lens for understanding the socio-technical dynamics of digital gambling. Practical implications include the need for adaptive regulations, responsible marketing practices, and empirical validation of conceptual frameworks to mitigate harm while sustaining consumer engagement.